Low-cost electronic DC load module design for battery capacity evaluation - Minh Nhat Huynh; Quoc Minh Lam; Cong Toai Truong; Huy Hung Nguyen; Van Tu Duong (HardwareX)
Rapid advancements in energy storage technology spurred by the use of electricity in a variety of applications have brought attention to the critical need for precise battery capacity evaluation. The electronic DC load devices play an important role in those tests by replicating real-world discharge conditions. However, commercial DC load systems are often prohibitively expensive and remain largely inaccessible to small enterprises, academic laboratories, and independent researchers. While open-source alternatives offer cost advantages, many existing designs lack scalability, flexibility, and ease of use. This study proposes a low-cost, modular electronic DC load capable of continuous operation at up to 50W per module. With its user-friendly interface and support for numerous other tests, including constant current, constant resistor, constant power, battery evaluation, and high-power pulse charge (HPPC) the proposed electronic DC load is robust and simple to use for battery research and evaluation.